2003
DOI: 10.1091/mbc.e03-02-0111
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Modulates Nucleolar Interaction of the Werner Protein with the AAA ATPase p97/VCP

Abstract: We report a novel nucleolar interaction between the AAA ATPase p97/VCP and the Werner protein (WRNp), a member of the RecQ helicase family. p97/VCP mediates several important cellular functions in eucaryotic cells, including membrane fusion of the endoplasmic reticulum and Golgi and ubiquitin-dependent protein degradation. Mutations in the WRN gene cause Werner syndrome, a genetic disorder characterized by premature onset of aging symptoms, a higher incidence of cancer, and a high susceptibility to DNA damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 66 publications
(72 reference statements)
3
86
0
3
Order By: Relevance
“…Several lines of evidence suggest that binding of alternative cofactors determines the specific role of VCP. Thus far, a number of VCP cofactors have been identified and regulate various VCP-mediated functions (35)(36)(37)(38)(39). Here we identify VCP as an Akt-binding protein and as an Akt substrate, suggesting a role for Akt in the regulation of VCP function.…”
mentioning
confidence: 67%
“…Several lines of evidence suggest that binding of alternative cofactors determines the specific role of VCP. Thus far, a number of VCP cofactors have been identified and regulate various VCP-mediated functions (35)(36)(37)(38)(39). Here we identify VCP as an Akt-binding protein and as an Akt substrate, suggesting a role for Akt in the regulation of VCP function.…”
mentioning
confidence: 67%
“…At present it is unclear how CDC-48 affects replication but recent studies reported that p97 binds to DNA replication factors (31,32). Interestingly, p97 associates with the human Werner RecQ helicase (33) and C. elegans CDC-48.1 with HIM-6, a Bloom Syndrome helicase homolog (34). As both RecQ helicases are involved in DNA replication to prevent accelerated aging, it is conceivable to speculate about an evolutionarily conserved requirement of CDC-48/p97 in DNA synthesis linked to cancer and longevity.…”
Section: Resultsmentioning
confidence: 99%
“…VCP has been implicated in a number of cellular events that are regulated during mitosis, including homotypic membrane fusion, spindle polar body function, and ubiquitindependent protein degradation. A proposed novel role for VCP is in the DNA damage response pathway through modulation of Werner protein (WRNp) availability in the nucleolus (Partridge et al, 2003). TREX1 is also involved in DNA repair mechanisms.…”
Section: Discussionmentioning
confidence: 99%